2006
DOI: 10.1097/01.ftd.0000197094.92559.b4
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Glucuronidation of Buprenorphine and Norbuprenorphine Determined by Liquid Chromatography-Electrospray Ionization-Tandem Mass Spectrometry

Abstract: The opioid partial agonist medication, buprenorphine (BUP), and its primary metabolite, norbuprenorphine (NBUP), are extensively glucuronidated. Sensitive analytical methods that include determination of buprenorphine-3-glucuronide (BUPG) and norbuprenorphine-3-glucuronide (NBUPG) are needed to more fully understand the metabolism and pharmacokinetics of buprenorphine. A method has now been developed that uses solid-phase extraction followed by liquid chromatography-electrospray ionization-tandem mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 22 publications
3
85
1
Order By: Relevance
“…2.6.1 Buprenorphine assay-Buprenorphine and metabolite concentrations were determined using a recently described liquid chromatography-tandem mass spectrometry (LC-MS/MS) method (Huang et al, 2006). Briefly, buprenorphine-d 4 and norbuprenorphine-d 3 were added to samples as the internal standards.…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…2.6.1 Buprenorphine assay-Buprenorphine and metabolite concentrations were determined using a recently described liquid chromatography-tandem mass spectrometry (LC-MS/MS) method (Huang et al, 2006). Briefly, buprenorphine-d 4 and norbuprenorphine-d 3 were added to samples as the internal standards.…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…MS/MS conditions used were 3.0 mTorr argon collision gas and 45 eV collision potential. When the Quantum was used, we found that norbuprenorphine had better sensitivity when the survivor molecular ion was monitored (i.e., 22 eV collision potential with m/z 414 to m/z 414) (Huang et al, 2006). The liquid chromatograph was a Hewlett-Packard Series 1100 HPLC (Agilent Technologies, Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The smaller difference between hydrolyzed M3 and nonhydrolyzed M3 (mean ϭ 68.5%, range 53-100% of unconjugated) suggests that it is excreted, for the most part, as the unconjugated form (Table 4). Nonhydrolyzed urine was also extracted by solid-phase extraction (Huang et al, 2006) to directly examine the conjugated buprenorphine and metabolites. Neutral loss scans of 176 (glucuronide conjugates) and 80 (sulfonate conjugates), and SRM (transition of molecular ion of interest to Ϫ176 and Ϫ80) were performed.…”
Section: Novel Metabolites Of Buprenorphinementioning
confidence: 99%
“…In general, the production of all three metabolites increased with increases in buprenorphine concentration, but there were some cases in which no norbuprenorphine or norbuprenorphine-3-glucuronide was detected at either of the concentrations of buprenorphine used (data not shown). The primary cultures of human hepatocytes did not replicate the formation of norbuprenorphine seen in humans or HLM incubated with buprenorphine supplemented with a source of NADPH (Moody et al, 2002;Chang and Moody, 2005;Huang et al, 2006). The potential for the intestines to form norbuprenorphine was determined by comparing production of buprenorphine metabolites in HLM and HSIM.…”
Section: Resultsmentioning
confidence: 99%
“…LC-ESI-MS/MS was performed essentially as described by Huang et al (2006). For hepatocyte culture media, 0.25-ml aliquots were used; for microsomal incubates, the entire mixture along with the methanol used to terminate the reaction was used.…”
Section: Lc-esi-ms/ms Enantiomer-selective Determination Of R-and S-mmentioning
confidence: 99%